The Borders of Albania from a Political, Geographical, Ethnic, and Military Point of View in the 1920s - Pacukaj, Sokol (European Journal of Multidisciplinary Studies, 2023)
The borders of Albania in the 1920s were a subject of political, geographical, ethnic, and military significance. Politically, Albania faced territorial disputes with neighboring countries, including Italy, Greece, and Yugoslavia, as they sought to expand their influence over Albanian territories. Geographically, the country’s borders encompassed diverse landscapes, ranging from the rugged mountains of the north to the coastal plains in the west and the inland regions in the east. Ethnically, the population consisted of various groups, including Albanians, Greeks, Serbs, and others, which added complexity to the question of border demarcation. From a military perspective, Albania’s limited resources and nascent armed forces posed challenges in defending its borders against external threats. This abstract provides an overview of the multidimensional nature of the borders of Albania in the 1920s, highlighting the political tensions, geographic diversity, ethnic complexities, and military considerations that shaped the country’s territorial integrity during that period.